Democracy's Detectives - The economics of investigative journalism - James T. Hamilton (Hardward university Press, 2018)
Investigative reporting generates new information about important issues that someone is trying to keep secret. Impacts of this journalism can be high. Yet the costs of discovering and telling these stories may also be significant. Democracy's Detectives uses economic theories of information to explain both how institutions breakdown in predictable ways and how journalists find and reveal which programs, products, and people go astray. The book analyzes the market for investigative reporting by examining more than 12,000 prize competition entries from 1979 to 2010 in the annual awards contest of Investigative Reporters and Editors. The results show what these investigative works in the United States uncovered and their impacts, and how the investigations were conducted and financially supported. Case studies of several investigative series demonstrate that each dollar invested in a story can yield hundreds of dollars in policy benefits. Examining the work of a Pulitzer prize-winning reporter shows how a single journalist over four decades generated more than 150 investigations that led to changes, including the passage of thirty-one state laws. Many valuable accountability stories go untold because media outlets bear the costs of reporting while the benefits spillover onto those who don't read or watch these investigations. Computational journalism may improve the economics of investigative reporting in two ways: lowering the cost of finding stories through better use of data and algorithms, and telling stories in more personalized and engaging ways. While breakdowns in institutions are inevitable, the combination of computation and journalism offers an expanded set of people new ways to hold those in power accountable and serve as democracy's detectives.-